2016
DOI: 10.1128/aac.00627-16
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Lefamulin Tested against Streptococcus pneumoniae with Defined Serotypes, Including Multidrug-Resistant Isolates Causing Lower Respiratory Tract Infections in the United States

Abstract: Lefamulin was evaluated against various Streptococcus pneumoniae serotypes that were collected from adults with lower respiratory tract infections. Lefamulin exhibited MIC 50 and MIC 90 values of 0.12 and 0.25 g/ml, respectively, against the entire collection (n ‫؍‬ 822). Similar results were obtained for lefamulin against each of the most common serotypes as well as against multidrug-resistant isolates and strains that are nonsusceptible to ceftriaxone or erythromycin. These data support the clinical developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
31
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 24 publications
2
31
0
2
Order By: Relevance
“…It contains arigid tricyclic carbon skeleton with eight stereogenic centers.R etapamulin is as emisynthetic derivative with athioether acetyl side chain and has been approved for topical S. aureus infections since 2007. [345,346] [344] Lefamulin (phase III) is an ovel thioether derivative,and represents the first systemic pleuromutilin antibiotic.…”
Section: Pleuromutilinsmentioning
confidence: 99%
See 1 more Smart Citation
“…It contains arigid tricyclic carbon skeleton with eight stereogenic centers.R etapamulin is as emisynthetic derivative with athioether acetyl side chain and has been approved for topical S. aureus infections since 2007. [345,346] [344] Lefamulin (phase III) is an ovel thioether derivative,and represents the first systemic pleuromutilin antibiotic.…”
Section: Pleuromutilinsmentioning
confidence: 99%
“…Thec ompound shows activity for respiratory pathogens and can be formulated for intravenous and oral treatment. [345,346]…”
Section: Pleuromutilinsmentioning
confidence: 99%
“…Fritsche, Z. Ivezic-Schoenfeld, and R. N. Jones, poster E-1183, presented at the 53rd Interscience Conference on Antimicrobial Agents and Chemotherapy, Denver, CO, 2013) which inhibits bacterial protein synthesis and growth by binding to the peptidyltransferase center of the 50S ribosomal subunit (interfering with 23S rRNA) with high affinity and specificity and uses different targets than do other antimicrobial classes (9). Lefamulin has completed a phase II clinical randomized controlled trial (RCT) for acute bacterial skin and skin structure infections and is currently undergoing two phase III RCTs for the treatment of community-acquired bacterial pneumonia (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…strains (13,14), and is currently in clinical development by Nabriva Therapeutics for treatment of community-acquired bacterial pneumonia. A previous study reported potent activity of lefamulin (MIC 90 , 0.006 g/ml) against 50 M. pneumoniae isolates from Germany, where macrolide resistance rates are low, but these organisms were not actually tested against macrolides for comparison (15).…”
mentioning
confidence: 99%